2019
DOI: 10.1093/jmcb/mjz051
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic motor CENP-E cooperates with PRC1 in temporal control of central spindle assembly

Abstract: Chromosome movements during mitosis are orchestrated primarily by the interaction of spindle microtubules with the kinetochore, the site for attachment of spindle microtubules to the centromere. Kinetochore‐associated mitotic kinesin CENP‐E plays key roles in chromosome congression and spindle checkpoint satisfaction. We have recently identified and characterized syntelin, a novel selective CENP‐E inhibitor (Ding et al., 2010. Cell Res. 20, 1386‐1390). Cells treated with syntelin progress through interphase, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…The fact that Lys191 is evolutionarily conserved from yeast to human suggest a functional conservation of Lys191 as an essential fitness machinery in eukaryotic cell division control while other two methylation sites may exhibit context-dependent regulation. It would be of great interest in the future studies to model the methylation site-specific function using physiological system such as organoids ( Liu et al, 2019 ; Yao and Smolka, 2019 ). Our present study delineated SET7/9 function in mitosis in which SET7/9-elicited methylation of PLK1 orchestrated phosphorylation kinetics at kinetochore for accurate chromosome alignment and segregation.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that Lys191 is evolutionarily conserved from yeast to human suggest a functional conservation of Lys191 as an essential fitness machinery in eukaryotic cell division control while other two methylation sites may exhibit context-dependent regulation. It would be of great interest in the future studies to model the methylation site-specific function using physiological system such as organoids ( Liu et al, 2019 ; Yao and Smolka, 2019 ). Our present study delineated SET7/9 function in mitosis in which SET7/9-elicited methylation of PLK1 orchestrated phosphorylation kinetics at kinetochore for accurate chromosome alignment and segregation.…”
Section: Discussionmentioning
confidence: 99%
“…By use of the CENP-E inhibitor syntelin, Ding and colleagues discovered that inhibition of CENP-E arrested cells in the prometaphase, with the chromosome syntelically attached to the spindle microtubules (71). Further delineation of CENP-E function in epithelial cell division in 3D organoids led the authors to uncover the role of CENP-E in central spindle organization (73). Surprisingly, the relocation of CENP-E from the kinetochore to the central spindle is regulated by BubR1 phosphorylation ( Figure 2B) (74).…”
Section: Kinetochore Plasticity Reorganization and Llpsmentioning
confidence: 99%
“…Three-dimensional images are compiled from successive light-sheet illuminations of thin, two-dimensional optical sections. The high spatial and temporal resolution of the imaging enables tracking of intracellular components in relatively thick samples, such as single chromosome trajectories in 3D gastric organoids ( Figure 6A) (73). At a higher magnification, compartments in a single chromosome can be visualized ( Figure 6B).…”
Section: Modeling Membrane Organelle Dynamics and Cell Fate In Organoidsmentioning
confidence: 99%
“…Previously, our group also demonstrated that the dynamic localization of Mps1 to the kinetochore is essential for accurate spindle microtubule attachment ( Dou et al, 2015 ). It would be of great interest, down the road, to model Mps1 function using recently established 3D organoids model combined with chemical biological tools ( Drost and Clevers, 2018 ; Liu et al, 2019 ; Yao and Smolka, 2019 ), which will unravel the context-dependent function of Mps1 such as pathogenesis of solid tumors.…”
Section: Discussionmentioning
confidence: 99%